Improving the Understanding of 3rd Grade Students of SD Negeri 11 Kepenuhan on the Pillars of Islam through the Role Playing Method in the Odd Semester of the 2024/2025 Academic Year - Suanto, Suanto (STKIP Rokania Pasir Pangaraian, 2024)
This classroom action research aims to improve the understanding of grade 3 students of SD Negeri 011 Kepenuhan on the material of the Five Pillars of Islam through the application of the role-playing method. The problem found was the low level of students' understanding of the five pillars of Islam, as indicated by the initial evaluation results and the lack of student involvement in the learning process. This research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data was collected through observation, formative tests, and documentation. The results showed a significant increase in student understanding from pre-action to the second cycle. The application of the role-playing method proved effective in improving the understanding of the concept of the Pillars of Islam because students were more active, enthusiastic, and easily remembered the material through fun activities.